Insights into the Pathology of the α2-Na+/K+-ATPase in Neurological Disorders; Lessons from Animal Models - Isaksen, Toke J.; Lykke-Hartmann, Karin (Frontiers in Physiology, 2016)
A functional Na+/K+-ATPase consists of a catalytic α subunit and a regulatory β subunit. Four α isoforms of the Na+/K+-ATPase are found in mammals, each with a unique expression pattern and catalytic activity. The α2 isoform, encoded by the ATP1A2 gene, is primarily found in the central nervous system (CNS) and in heart-, skeletal- and smooth muscle tissues. In the CNS, the α2 isoform is mainly expressed in neuroglial cells. In particular, the α2 isoform is found in astrocytes, and is important for astrocytic K+ clearance and, consequently, the indirect uptake of neurotransmitters. Both processes are essential for proper brain activity, and autosomal dominantly mutations in the ATP1A2 gene cause the neurological disorder Familial hemiplegic migraine type 2 (FHM2). FHM2 is a severe subtype of migraine with aura that involving temporary numbness or weakness, and affecting only one side of the body. FHM2 patients often suffer from neurological comorbidities such as seizures, sensory disturbances, cognitive impairment and psychiatric manifestations. The functional consequences of FHM2 disease mutations leads to a partial or complete loss of function of pump activity; however a clear phenotype-genotype correlation has yet to be elucidated. Gene-modified mouse models targeting the Atp1a2 gene have proved instrumental in the understanding of the pathology of FHM2. Several Atp1a2 knockout (KO) mice targeting different exons have been reported. Homozygous Atp1a2 KO mice die shortly after birth due to respiratory malfunction resulting from abnormal Cl- homeostasis in brainstem neurons. Heterozygous KO mice are viable, but display altered behavior and neurological deficits such as altered spatial learning, decreased motor activity and enhanced fear/anxiety compared to wild type mice. FHM2 knock-in (KI) mouse models carrying the human in vivo disease mutations W887R and G301R have also been reported. Both models display altered cortical spreading depression (CSD) and points to deficits in the glutamatergic system as the main underlying mechanism of FHM2.